AMBIGUITY IN THE STRUCTURE OF THE THREE STAND-UP COMEDIANS' RULE: A DISAMBIGUATING STIMULUS FOR HUMOR - Elsara Khairun Nisa; Rustono; Tommi Yuniawan; Rahayu Pristiwati (English Review: Journal of English Education, 2026)
The phenomenon of stand-up comedy relies heavily on linguistic manipulation to generate laughter. While ambiguity has been studied in various humor contexts, no research has specifically examined how Indonesian stand-up comedians exploit ambiguity within the rule of three structure to trigger disambiguation and create humorous effects. This study aims to analyze the types of ambiguity (lexical, structural, and situational) used in the rule of three pattern, describe the linguistic strategies employed to build and resolve ambiguity, and examine how disambiguation contributes to humor. Using a qualitative descriptive-analytical approach, data were collected from stand-up comedy performances on YouTube, transcribed, and analyzed using relevance theory. The findings reveal that comedians deliberately construct initial expectations in the first two sequences before introducing ambiguity in the third sequence (punchline). This ambiguity forces audiences to disambiguate sociocultural concepts such as educational quality, social piety, and economic status, with successful disambiguation producing laughter. The study concludes that ambiguity in stand-up comedy functions as a precise stylistic instrument for deconstructing conventional logic and social norms. Future research should explore sociolinguistic dimensions affecting disambiguation speed across different audience backgrounds.